Compliance: um estudo bibliométrico sobre a aplicação dessas práticas na indústria de óleo e gás - Pires Antunes, João Vitor; Padovani Xavier, Thiago; Zuliani Mantegazini, Diunay (Latin American Journal of Energy Research, 2023)
The term compliance, which, in English, means conformity, began to have greater perception from the 2000s onwards, due to the appearance of non-compliance scandals, particularly in American companies. Companies in the oil and gas (O&G) sector were one of the main targets of Operation Lava Jato and to respond strategically in order to restore their reputation, the sector created the Compliance Commission of the Brazilian Institute of Petroleum, Gas and Biofuels (IBP), made up of the main O&G companies and the Ethos Institute. Initiative that resulted in the production of the Integrity Pact for the Oil, Gas and Biofuels Industry and the Good Practices Guide. Since the importance of applying the practice of compliance in the specific sector is known, but it is not known how much research is done on it, bibliometric research would be able to have this understanding and investigate how companies respond to the application of this practice, which, apparently, this return of companies has not yet been much investigated by surveys. For this purpose, the research was carried out using the Web of Science database, where in the first stage of the research, when the first term “compliance” was used alone, 41,097 articles published in the last 10 years were found, which are in magazines from all continents, but concentrated in the USA and England. By restricting the search and adding the second term, defining the industrial branch in which it is desired to research compliance, oil and gas, the search resulted in 108 articles. As the number was still higher than 10, the search was restricted to the 10 most cited articles out of the 108 resulting from the search with the second term. Only 2 of the 10 most cited articles used the term compliance as corporate governance, which is the intent here.